Simultaneous Energy Storage and Seawater Desalination using Rechargeable Seawater Battery: Feasibility and Future Directions. Issue 18 (28th July 2021) - Son, Moon; Park, Sanghun; Kim, Namhyeok; Angeles, Anne Therese; Kim, Youngsik; Cho, Kyung Hwa
Abstract: Rechargeable seawater battery (SWB) is a unique energy storage system that can directly transform seawater into renewable energy. Placing a desalination compartment between SWB anode and cathode (denoted as seawater battery desalination; SWB‐D) enables seawater desalination while charging SWB. Since seawater desalination is a mature technology, primarily occupied by membrane‐based processes such as reverse osmosis (RO), the energy cost has to be considered for alternative desalination technologies. So far, the feasibility of the SWB‐D system based on the unit cost per desalinated water ($ m −3 ) has been insufficiently discussed. Therefore, this perspective aims to provide this information and offer future research directions based on the detailed cost analysis. Based on the calculations, the current SWB‐D system is expected to have an equipment cost of ≈1.02 $ m −3 (lower than 0.60–1.20 $ m −3 of RO), when 96% of the energy is recovered and stable performance for 1000 cycles is achieved. The anion exchange membrane (AEM) and separator contributes greatly to the material cost occupying 50% and 41% of the total cost, respectively. Therefore, future studies focusing on creating low cost AEMs and separators will pave the way for the large‐scale application of SWB‐D. Abstract : Seawater battery desalination (SWB‐D) is a multifunctional system capable of storing energy and removing salt from water simultaneously. This perspective lays out a detailed cost analysis of the system, and provides an insight as to where SWB‐D currently stands in terms of its feasibility and what areas need to be improved to realize large scale applications.